In situ coating nickel organic complexes on free-standing nickel wire films for volumetric-energy-dense supercapacitors. (4th May 2018) - Hong, Min; Xu, Shusheng; Yao, Lu; Zhou, Chao; Hu, Nantao; Yang, Zhi; Hu, Jing; Zhang, Liying; Zhou, Zhihua; Wei, Hao; Zhang, Yafei
Abstract: A self-free-standing core-sheath structured hybrid membrane electrodes based on nickel and nickel based metal-organic complexes (Ni@Ni-OC) was designed and constructed for high volumetric supercapacitors. The self-standing Ni@Ni-OC film electrode had a high volumetric specific capacity of 1225.5 C cm −3 at 0.3 A cm −3 and an excellent rate capability. Moreover, when countered with graphene-carbon nanotube (G-CNT) film electrode, the as-assembled Ni@Ni-OC//G-CNT hybrid supercapacitor device delivered an extraordinary volumetric capacitance of 85 F cm −3 at 0.5 A cm −3 and an outstanding energy density of 33.8 at 483 mW cm −3 . Furthermore, the hybrid supercapacitor showed no capacitance loss after 10 000 cycles at 2 A cm −3, indicating its excellent cycle stability. These fascinating performances can be ascribed to its unique core-sheath structure that high capacity nano-porous nickel based metal-organic complexes (Ni-OC) in situ coated on highly conductive Ni wires. The impressive results presented here may pave the way to construct s self-standing membrane electrode for applications in high volumetric-performance energy storage.